Perbedaan Qira’at Imam Nafi’ dan Imam Hamzah Dalam Surah al-Dhuha - Azmi, Khairul; Iskandar (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2024)
This study aims to analyse the differences between the Qira'at of Imam Nafi' and Imam Hamzah in Surah Al-Duha. Qira'at is a variation in the recitation of the Qur'an that is permitted by the Shari'ah and has distinctive characteristics. Surah Al-Duha, as one of the Makkiyah Surah, provides a clear example of this variation. This study uses an analytical descriptive method to compare aspects of the two Imams' recitations, including differences in letter pronunciation, intonation and tajwid. The results show that there are significant differences in some verses of Surah Al-Duha involving variations in recitation that affect the meaning and way of understanding the Quranic text. This study is expected to provide a deeper understanding of qira'at and its contribution to the rich tradition of Quranic recitation.